The COMPARISON BETWEEN HYPERBARIC BUPIVACAINE PLUS FENTANYL AND HYPERBARIC BUPIVACAINE ALONE IN SPINAL ANESTHESIA FOR CAESAREAN SECTION - Iqbal, Fatima; Faridi, Manzoor Ahmed; Saeed, Aisha; Shah, Inamullah (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare the result of the combination of hyperbaric bupivacaine plus fentanyl with hyperbaric bupivacaine alone in patients undergoing caesarean section in spinal anaesthesia. Study Design: Comparative, cross-sectional study. Place and Duration of Study: Department of Anesthesia, Fauji Foundation Hospital, Rawalpindi Pakistan, from Dec 2017 to Jun 2018. Methodology: After consulting the institutional ethical review committees a total of 60 females between ages 18-40 years were enrolled for caesarean section delivery. They were divided into two groups. The study group (n=30) received a subarachnoid injection of 0.5% hyperbaric bupivacaine (10mg) 2ml with 25ug of fentanyl 0.5ml and control group (n=30) was injected 0.5% hyperbaric bupivacaine 12.5mg (2.5 ml) only. Pain experienced during the procedure was assessed by using 10-point visual analogue scoring method. The mean duration of analgesia, mean arterial blood pressure and heart rate after surgery were compared between two groups. Results: The mean duration of analgesia was 206.5/min ± 6.4 in the study group and it was 163.6min ± 7.2 in the control group (p=0.001). Mean arterial BP after surgery was 92.3mmHg ± 3.8 in the study group and 88.7mmHg ± 4.1 in the control group (p=0.001). The mean heart rate recorded after surgery was 75.2/min ± 5.2 in the study group and it was 70.4/min ± 6.1 in the control group (p=0.001). Conclusions: The mean duration of analgesia was significantly longer in the study group when compared with the control group with better mean arterial blood pressure and heart rate response after Caesarean section.